A Comparative Analysis of Survival and Funding Discrepancies in Cancers With High Mortality. Issue 2 (February 2020) - Hall, Bradley R.; Cannon, Andrew; Atri, Pranita; Wichman, Christopher S.; Smith, Lynette M.; Kumar, Sushil; Batra, Surinder K.; Wang, Hongmei; Ganti, Apar Kishor; Sasson, Aaron R.; Are, Chandrakanth
Abstract : Objective: Comparative analyses of survival and funding statistics in cancers with high mortality were performed to quantify discrepancies and identify areas for intervention. Background: Discrepancies in research funding may contribute to stagnant survival rates in pancreatic ductal adenocarcinoma (PDAC). Methods: The Surveillance, Epidemiology, and End Results database was queried for survival statistics. Funding data were obtained from the National Cancer Institute (NCI). Clinical trial data were obtained from www.clinicaltrials.gov . Cancers with high mortality were included for analyses. Results: Since 1997, PDAC has received lesser funding (1.41 billion) than other cancers such as breast (10.52 billion), prostate (4.93 billion), lung (4.80 billion), and colorectal (4.50 billion). Similarly, fewer clinical trials have been completed in PDAC (n = 608) compared with breast (n = 1904), lung (n = 1629), colorectal (n = 1080), and prostate (n = 1055) cancer. Despite this, since 1997, dollars invested in PDAC research produced a greater return on investment with regards to 5-year overall survival (5Y-OS) compared with breast, prostate, uterine, and ovarian cancer. Incremental cost-effectiveness analysis demonstrates that millions (liver, non-Hodgkin lymphoma, and melanoma) and billions (colorectal and lung) of dollars were required for each additional 1% increase in 5Y-OS compared with PDAC. Funding of research towards early diagnosis of PDAC has decreased by 19% since 2007. For nearly all cancers, treatment-related research receives the highest percentage of NCI funding. Conclusions: Funding of PDAC research is significantly less than other cancers, despite its higher mortality and greater potential to improve 5Y-OS. Increased awareness and lobbying are required to increase funding, promote research, and improve survival. Abstract : Supplemental Digital Content is available in the text